REVIEW OF THE NEOTECTONICS OF THE EASTERN TURKISH-ARMENIAN PLATEAU BY GEOMORPHIC ANALYSIS OF DIGITAL ELEVATION MODEL IMAGERY - Dhont D.; Chorowicz J. (My University, 2006)
Digital elevation model (DEM) images provide synoptic views of the Earth's surface allowing the analysis of landforms of still active tectonic and volcanic structures at regional scale. A DEM at 250 m pixel size constitutes regional scale data particularly efficient to investigate the late Miocene-Quaternary deformation of the Eastern Turkish-Armenian Plateau in the Arabian-Eurasian area of convergence. Geomorphic analysis of the DEM image associated with review of fault-plane solutions of earthquakes show that faults are mostly strike-slip with small vertical component. Here we show that the orientations of the tectonic and volcanic structures fit with a tectonic regime characterized by N-S shortening and E-W lengthening, consistent with westward escape of Anatolia perpendicular to the direction of the Arabia-Eurasia shortening. The uniform uplift of the plateau, the predominance of strike-slip faulting, the lack of major thrusts and the occurrence of normal faults do not support a model of going-on crustal thickening due to intracontinental convergence. On the contrary, our observations can be better interpreted in terms of lithospheric thinning and mantle upwelling related to gravity escape of Anatolia. © Springer-Verlag 2005.
Keywords: ANATOLIA; DEM; ESCAPE TECTONICS; NEOTECTONICS; UPLIFT; Quaternary; Miocene; Cenozoic::Quaternary; Кайнозой::Четвертичная; Cenozoic::Neogene::Miocene; Кайнозой::Неоген::Миоцен